Polyetherimide hollow fiber membranes for CO2 absorption and stripping in membrane contactor application - Rosmawati, Naim; A. F., Ismail; Matsuura, T.; Izzati, Ahmad Rudaini; Syamsul Bahari, Abdullah (Royal Society of Chemistry, 2018)
Porous asymmetric polyetherimide (PEI) hollow fiber membranes with various non-solvent additives, e.g. lithium chloride, methanol and phosphoric acid (PA) were prepared for CO2 absorption and stripping process in a membrane contractor. The PEI membranes were characterized via gas permeation, liquid entry pressure of water (LEPw), contact angle and field emission scanning electronic microscopy analysis. The CO2 absorption and stripping performance was evaluated via the membrane contactor system. Addition of non-solvent additives increased the LEPw and membrane porosity of the PEI membrane with the formation of various membrane microstructures and contact angles. Absorption test was performed at 40 °C showed that the PEI–PA membrane produced the highest absorption flux of 2.7 × 10−2 mol m−2 s−1 at 0.85 m s−1 of liquid velocity. Further testing on PEI–PA membrane was conducted on CO2 stripping at 60 °C, 70 °C to 80 °C and the results indicated that the stripping flux was lower compared to the absorption flux. Stripping tests at 80 °C produced the highest stripping flux which might due to the increase in equilibrium partial pressure of CO2 in the liquid absorbent. Modification of PEI membrane via incorporation of additive can enhanced the performance of a membrane contactor via increasing the absorption and stripping flux.